The effects of GpcB1 locus on high grain protein concentration introgressed into Argentinean wheat germplasm - Tabbita, Facundo (2012)
Wheat grain protein content (GPC) is important for human nutrition and has a strong influence on the quality of pasta and bread. The objective of this study was to analyse the introduction of the Gpc-B1 allele into two Argentinean bread wheat cultivars. Near-isogenic lines were developed in ?ProINTA Oasis? and ?ProINTA Granar? using marker-assisted selection. Gpc-B1 lines showed a significant (P = 0.01) increase in GPC and a significant (P = 0.001) decrease in grain weight in comparison with control lines without Gpc-B1. Differences in yield were not significant (P = 0.49) between lines. Gpc-B1 lines significantly reduced (P = 0.02) straw nitrogen concentration at maturity and significantly increased (P = 0.02) the nitrogen harvest index. When data were analysed by genotype and environment, differences in some analysed parameters were found, indicating that Gpc-B1 expression may be affected by different genetic backgrounds and environmental conditions. These results suggest that the introgression of the Gpc-B1 allele into Argentinean wheat germplasm could be a valuable resource for improving GPC with no detrimental effect on grain yield.